Waste Management Environmental Campaign at Bunga Bangsa High School Bandung in Support of Strengthening SDGs Point Number 12 - Rizky Ilhami; Muhammad Fazri Candra; Soma Gantika; Andi Sukandi (Lembaga Pengembangan Kinerja Dosen, 2024)
Expanding their perspectives helps students comprehend the linkages between several subjects and the global context. They can hone their critical thinking abilities, investigate various viewpoints, and enlarge their horizons. Therefore, expanding horizons through the delivery of knowledge in a fresh perspective and scope is necessary to increase the quality of competent students. The goal of Bunga Bangsa High School's waste management campaign programme is to raise students' awareness of the urgency of the current climate catastrophe. through a range of exercises, talks, and workshops, among other things. The exercises are designed to provide participants a comprehensive grasp of the significance of waste management by shedding light on environmental challenges. This programme, which incorporates students actively in the campaign, aims to implement Sustainable Development Goal (SDG) number 12, Responsible Consumption and Production, by fostering a deeper understanding of the waste management process, from personal to industrial waste, particularly in Bandung City.